Perekrutan Karyawan Menggunakan Algoritme TOPSIS dan Pengujian UAT - Siswanto Siswanto; Muhammad Satria Al Aziz; Mujito Mujito; Basuki Hari Prasetyo (Prosiding SISFOTEK, 2020)
The problem at PT. Putra Bangsingja Perkasa has difficulty in providing employee recommendations that are accepted according to the needs of the 160 prospective employees who register every 6 months of employee recruitment and who assess only 2 people. Employee recruitment applications using the TOPSIS algorithm need to be made to recommend employees who really meet the quality and match the desired criteria such as physical appearance, comprehension, communication, work motivation, education and work experience. The final results of this study are the results of the UAT testing process, the respondents agree (above 83.3%) that overall this employee recruitment application helps the leadership in providing employee recommendations that are accepted according to their needs.